HUMANITAS 104: LA IGLESIA DEL CARDENAL. - VALENZUELA C., EDUARDO (Humanitas (07172168))
The article "HUMANITAS 104: THE CARDINAL'S CHURCH" focuses on the figure of Cardinal Raúl Silva Henríquez and his role in the Chilean Church before and after the military coup of 1973. The cardinal was a defender of human rights and solidarity with the poorest. He sought a Church committed to the social and human problems of his time, promoting reforms in the liturgy and the social doctrine of the Church. He also promoted the participation of the laity in pastoral tasks and the creation of educational, social, communicational, and economic organizations to strengthen the social influence of the Church. The author laments that the Catholic University is the only institution of the Church that has acquired social relevance in the last forty years, while others have languished or disappeared. It is mentioned that efforts to create another university were unsuccessful due to the risk of compromising the Church's social work with external political projects. The author highlights the importance of preserving the evangelical peculiarity of the Church in its projects.